2011
DOI: 10.1111/j.1523-1739.2011.01747.x
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Effect of Tasmanian Devil Facial Tumor Disease at the Disease Front

Abstract: Pathogen-driven declines in animal populations are increasingly regarded as a major conservation issue. The Tasmanian devil (Sarcophilus harrisii) is threatened with extinction by devil facial tumor disease, a unique transmissible cancer. The disease is transmitted through direct transfer of tumor cells, which is possible because the genetic diversity of Tasmanian devils is low, particularly in the major histocompatibility complex genes of the immune system. The far northwest of Tasmania now holds the last rem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
95
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 74 publications
(100 citation statements)
references
References 36 publications
4
95
1
Order By: Relevance
“…There were insufficient data to include any interactions with sex; however, no study has previously reported an effect of sex in the epidemiology of DFTD or in the likelihood of infection [16,20,22]. Tumours of unknown karyotypes and those with evidence of both diploid and tetraploid karyotypes were pooled as there were insufficient data to model them separately, and animals were only included in the analysis on the first occasion that they were captured with a tumour-given that all tumours sampled more than once (11 tetraploid and 18 diploid) kept their original karyotype, subsequent recaptures were omitted.…”
Section: (C) Statistical Analysesmentioning
confidence: 99%
See 4 more Smart Citations
“…There were insufficient data to include any interactions with sex; however, no study has previously reported an effect of sex in the epidemiology of DFTD or in the likelihood of infection [16,20,22]. Tumours of unknown karyotypes and those with evidence of both diploid and tetraploid karyotypes were pooled as there were insufficient data to model them separately, and animals were only included in the analysis on the first occasion that they were captured with a tumour-given that all tumours sampled more than once (11 tetraploid and 18 diploid) kept their original karyotype, subsequent recaptures were omitted.…”
Section: (C) Statistical Analysesmentioning
confidence: 99%
“…This is accompanied by severe declines in individual survival rates and population growth rates, leading to regional-scale decline in population size of more than 90% [22], as well as collapse of age structure [23,24]. At WPP, disease prevalence remained low (less than 20% in adults; less than 10% in juveniles), there was no population decline, and age structure remained unaltered for up to 4 years following the outbreak [20]. Inexplicably, DFTDinfected individuals at WPP had higher survival rates than those in eastern populations [20].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations